Brucella Periprosthetic Joint Infection Involving Bilateral Knees with Negative Synovial Fluid Alpha-Defensin. (14th July 2019) - Balkhair, Abdullah; Al Maskari, Sultan; Ibrahim, Shadin; Al Busaidi, Ibrahim; Al Amin, Mohammed; Ba Taher, Hashim
Abstract : Periprosthetic joint infection (PJI) due to Brucella is uncommon despite relatively high endemicity of human brucellosis and its osteoarticular predilection. We report a case of a 57-year-old woman with bacteraemic brucellosis complicated by Brucella periprosthetic infection of both knee joints occurring a decade after bilateral knee arthroplasty and associated with a negative synovial fluid alpha-defensin test. The patient was successfully treated with anti- Brucella therapy alone and without surgical revision, resulting in clinical and microbiological cure. We propose that Brucella should be considered as a possible cause of prosthetic joint infection in the appropriate clinical and epidemiological settings. A negative synovial fluid alpha-defensin (Synovasure AD test) should not be used as a rule-out test for Brucella PJI. Brucella PJI without radiological loosening may be treated conservatively and solely with antimicrobial therapy.